Sozial-dokumentarische Photographie In den USA - Doherty, R.J. (Luzern : Bucher, 1974)
Riis, Jacob A. ; Hine, Lewis W. ; Lange, Dorothea ; Rothstein, Arthur ; Mydans, Carl ; Shahn, Ben ; Delano, Jack ; Lee, Russell ; Palmer ; Parks, Gordon ; Carter, Paul ; Collier, John ; Vachon, John.
Schenking Eric de Kuyper
boek